2014
DOI: 10.1590/s1806-66902014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação físico-química e comportamento higroscópico de goiaba em pó obtida por spray-dryer

Abstract: * RESUMO -A goiaba é uma das frutas tropicais mais populares e de maior aceitação em todas as regiões do Brasil. Do seu fruto podem-se obter vários produtos alimentícios tais como: doces, geleias, licores e sucos de diversas formas. Diante do exposto, o objetivo desta pesquisa foi caracterizar a polpa de goiaba atomizada quanto à sua composição físico-química e, avaliar o seu comportamento higroscópico através das isotermas de adsorção utilizando diferentes modelos matemáticos. As análises físico-químicas real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
15

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 6 publications
3
5
0
15
Order By: Relevance
“…This same behavior was also observed by Santos et al (2014) while studying guava powder obtained in spray-dryer.…”
Section: Resultssupporting
confidence: 82%
“…This same behavior was also observed by Santos et al (2014) while studying guava powder obtained in spray-dryer.…”
Section: Resultssupporting
confidence: 82%
“…Oliveira et al (2014), working with lyophilized yellow mombin powder, observed that the BET model promoted the best adjustment for the whole yellow mombin pulp powder, while the model of Henderson was the best to represent the isotherm of the sample containing maltodextrin. Santos et al (2014), for guava powder obtained through spray dryer, observed that the model of Henderson showed the best adjustment at all the evaluated temperatures. Oliveira et al (2013), studying the hygroscopic behavior of lyophilized powder of grugru palm (Acrocomia aculeata), observed that the models of GAB and Oswin showed the best adjustment to the experimental data of isotherms of the powder without the addition of maltodextrin and mixed with 8% of maltodextrin, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…According to Oliveira et al (2014a), the Henderson model was one of the best models to predict the isotherm of atomized 'macauba' powder with 8% maltodextrin and water activity between 0.3 and 0.7. The Henderson model was also reported as the best model to predict isotherms in other works, such as those carried out by Mil et al (2014) on atomized mango pulp powder and by Santos et al (2014) on atomized guava pulp powder.…”
Section: Resultsmentioning
confidence: 84%
“…The lyophilized 'mangaba' pulp powder presented soluble solid contents greater than those of other dehydrated products. Santos et al (2014) found soluble solid contents of 93 ºBrix in atomized guava powder, while Oliveira et al (2014b) Oliveira et al (2011), besides the content of sugars, the porosity and soluble compounds of lyophilized foods also contribute to increasing their water content. Powders are susceptible to different physical changes according to the relative humidity of their environment.…”
Section: Resultsmentioning
confidence: 97%